2016
DOI: 10.1590/1809-4430-eng.agric.v36n6p1096-1109/2016
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Strategies With Water Deficit in ‘Tommy Atkins’ Mango Tree

Abstract: ABSTRACT:With the limited availability of water in semi-arid regions, it is necessary that irrigation is accurate and there is high water use efficiency.This study aimed to evaluate the regulated deficit irrigation (RDI) and partial rootzone drying (PRD) in yield, water use efficiency and gas exchange of 'Tommy Atkins' mango tree in semi-arid conditions. The experimental design was a randomized block with seven treatments for RDI under micro sprinkler and five treatments for the PRD under drip. Treatments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…O método da RDI tem sido avaliado em mangueira (SANTOS et al, 2016b;COTRIM et al, 2017) como em várias outras culturas; mas ainda não foi avaliado em bananeira, que é de maior consumo de água. O emprego do método exige o conhecimento das fases fenológicas da cultura e particularmente das fases fenológicas de maior e menor demanda de água pelas plantas.…”
Section: Introductionunclassified
“…O método da RDI tem sido avaliado em mangueira (SANTOS et al, 2016b;COTRIM et al, 2017) como em várias outras culturas; mas ainda não foi avaliado em bananeira, que é de maior consumo de água. O emprego do método exige o conhecimento das fases fenológicas da cultura e particularmente das fases fenológicas de maior e menor demanda de água pelas plantas.…”
Section: Introductionunclassified
“…In recent years, the related research on RDI had been gradually increased and enriched, and it had been tested or applied in a variety of crops. Such as citrus (Gonzalez-Dugo et al 2018 ; Romero-Trigueros et al 2017 , 2020 ), grape (da Silva et al 2018 ; Guo et al 2021 ; Ju et al 2019 ), blueberry (Keen and Slavich 2012 ; Lobos et al 2016 ), pear (Lepaja et al 2018 ; Wu et al 2020 ), mango (Dos Santos et al 2016 , 2020 ), peach (Falagan et al 2016 ; Manuel Miras-Avalos et al 2016 , 2017 ), melon (Lamaoui et al 2018 ; Zeinalipour et al 2017 ) and other fruits, as well as tomato (Bogale et al 2016 ; Coyago-Cruz et al 2019 ; Hooshmand et al 2019 ; Wang and Zhang 2014 ), lettuce (Chang et al 2021 ; Lin et al 2020 ), sugar beet (Abyaneh et al 2017 ; Li et al 2019 ), cauliflower (Abdelkhalik et al 2019a ; Hachmann et al 2019 ), pepper (Abdelkhalik et al 2020 ; Yang et al 2018 ), potato (Xie et al 2012 ) and other vegetables. Some food crops such as wheat (El-Sanatawy and Zedan 2020 ; Ma et al 2019 ; Zhang et al 2021 ), maize (Ma et al 2016 ; Salem et al 2021 ) and horticultural flowers such as marigold flower (Yasheshwar et al 2017 ) also had related studies on the application of RDI.…”
Section: Definition and Main Approaches Of Rdimentioning
confidence: 99%
“…In this way, nutrients and photoassimilates are targeted for reproductive development. However, more severe deficits compromise the photosynthetic rate (Santos et al, 2016), causing a significant reduction in yield, as observed in the PRD with the application of 40% ETc.…”
Section: Yield and Water Use Efficiency Of 'Palmer' Mangomentioning
confidence: 99%
“…In the mango crop, the RDI and PRD strategies have been investigated (Spreer et al, 2007;Spreer, Ongprasert, Hegele, Wunsche, & Muller, 2009), Srikasetsarakul et al (2015); Santos, Donato, Faria, Coelho and Cotrim (2016) and shown results that indicate water and energy savings, improved fruit quality and maintenance of yield.…”
Section: Introductionmentioning
confidence: 99%